Analysis of 401 Cases of Gestational Trophoblastic Disease (GTD) at Bangabandhu Sheikh Mujib Medical University (BSMMU) - Khatun, Sabera; Ferdous, Jannatul; Khatun, Fatema; Khatun, Rahima; Begum, Monowara; Faika, Jakanta; Akhter, Latifa (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Gestational Trophoblastic Disease (GTD) form a group of early pregnancy related disorders spanning the conditions of complete and partial molar pregnancies, through to the malignant conditions of invasive mole, choriocarcinoma and very rare placental site trophoblastic tumor (PSTT). In the U.K there exists an effective registration and treatment programme for GTD. The programme has achieved impressive results with high cure rate (98-100%) and low (5-8%) chemotherapy rate for the management of GTD. At Bangabandhu Sheikh Mujib Medical University similar type of GTD center run at the Department of Gynaecological Oncology, since 1998. Objective: To understand the importance of management of patients with GTD in accordance to the international standard level of care and the importance of establishment of specific center for GTD. Method: Study population were the diagnosed cases of GTD both clinically and radiologically who attended the gynae oncology department of BSMMU. All the cases were managed following an international standard protocol. Total 603 cases were registered in a predesigned “Gestational Trophoblastic Disease Molar Card. Due to incomplete data only 401 cases were statistically analysed by SPSS version 22. Results: Maximum (59.6%) population were at 15-25 years age group. Blood group distribution were almost similar O+ve 27.7%, B+ve 27.7%, A+ve 24.7%. Primigravida were 38.2% cases. Rural women were 67%. Sixty seven percent cases had suction evacuation & curettage at the gynaecological oncology department of BSMMU. Second curettage (check D&C) required in 40% cases, 91% cases had incomplete follow up. Age distribution according to follow-up showed that young women (21-25 years) had maximum follow up. Seventy percent women did not require chemotherapy and 81% women of more than 40 years age required chemotherapy, only 7% women had hysterectomy for molar pregnancy, one of them had cervical cancer with molar pregnancy. Mortality among 603 cases were nil. Conclusion: Outcome of management of molar pregnancy depends on complete evacuation of mole, proper follow-up at regular interval and timely decision regarding hysterectomy and chemotherapy for persistent gestational trophoblastic neoplasia. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 3-11